Beatification and Canonization Procedures on Account of oblationes vitae - Kiwior, Wiesław (Prawo Kanoniczne, 2025)
Through the processes of beatification and canonisation, the Catholic Church presents its faithful with models of holiness and intercessors before God. Until 2017, those were martyrs (those who were killed for their faith or for a virtue flowing from that faith) and confessors (those who practised Christian virtues heroically), and on 11th July 2017 Pope Francis, in his apostolic letter in the form of a motu proprio Maiorem hac dilectionem, introduced another manifestation of canonised holiness, namely the heroic offering of one’s life propter caritatem. The author referred to the criteria of martyrdom and heroic practice of Christian virtues and presented the specifics of the new cause for beatification and canonisation (a free and voluntary offer of life and heroic acceptance propter caritatem of a certain and untimely death; a nexus between the offer of life and premature death; the exercise, at least as ordinarily possible, of Christian virtues; the existence of a reputation of holiness and of signs; the necessity of a miracle occurring through the intercession of the Servant of God) and the current status of all beatification and canonisation cases currently pending under this cause. During the eight years of validity of the new regulations, thirteen cases occurred in the Church on account of the newly introduced cause, one of which concerns a group of five priests who sacrificed their lives serving the sick and dying during a yellow fever epidemic, as a result of which they all contracted the disease and died. Of all the cases, five ended with the promulgation of the super oblatione vitae decree, three cases are being examined at the Roman stage, and five cases are being processed at the diocesan stage. The author emphasises that the introduction of a new cause for beatification and the related change of the original causes in seven cases initiated before the new regulations came into force indicate the usefulness of the new cause in beatification and canonisation cases and that the selection of an appropriate cause in a specific case must be preceded by a thorough examination of all the circumstances of the case in the light of the criteria specific to each cause.